2021
DOI: 10.1038/s41598-021-82350-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of FGF5-induced cell proliferation by RNA aptamers

Abstract: Fibroblast growth factor 5 (FGF5) is a crucial regulator of hair growth and an oncogenic factor in several human cancers. To generate FGF5 inhibitors, we performed Systematic Evolution of Ligands by EXponential enrichment and obtained novel RNA aptamers that have high affinity to human FGF5. These aptamers inhibited FGF5-induced cell proliferation, but did not inhibit FGF2-induced cell proliferation. Surface plasmon resonance demonstrated that one of the aptamers, F5f1, binds to FGF5 tightly (Kd = 0.7 ± 0.2 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…An RNA aptamer that binds FGF5 with high affinity was shown to inhibit FGF5‐induced cell proliferation, but not FGF2‐induced cell proliferation. As mutations or knockout of Fgf5 results in abnormally long hair, this aptamer may be useful to enhance hair growth (Amano et al, 2021; Hébert et al, 1994).…”
Section: Development Of Fgf Pathway Inhibitors As Pharmaceuticalsmentioning
confidence: 99%
“…An RNA aptamer that binds FGF5 with high affinity was shown to inhibit FGF5‐induced cell proliferation, but not FGF2‐induced cell proliferation. As mutations or knockout of Fgf5 results in abnormally long hair, this aptamer may be useful to enhance hair growth (Amano et al, 2021; Hébert et al, 1994).…”
Section: Development Of Fgf Pathway Inhibitors As Pharmaceuticalsmentioning
confidence: 99%
“…Finally, recognizing the importance of FGF5 overexpression in oncogenic processing, RNA aptamers that inhibit FGF5 expression have been proposed as a potential therapy for cancers dependent on FGF5 cell proliferation. 43 The protein structure modeling results do not provide an indisputable mechanism for pathogenicity of the W81C mutation reported here; the overall and local structural changes observed are modest at best. Nonetheless, the prediction of a second binding site for SO 4 in the mutant, albeit with a smaller multiplicity, may be an indication that the mutant's ability to bind to SO 4 -containing compounds, like heparan sulfate, may be different.…”
Section: S X 60smentioning
confidence: 57%
“…Zhou 41 reported that downregulation of FGF5 inhibits cell growth and invasion of human nonsmall cell lung cancer cells, and Zhao 42 has documented that increase of FGF5 expression correlates with poor survival in lung adenocarcinoma. Finally, recognizing the importance of FGF5 overexpression in oncogenic processing, RNA aptamers that inhibit FGF5 expression have been proposed as a potential therapy for cancers dependent on FGF5 cell proliferation 43 …”
Section: Discussionmentioning
confidence: 99%
“…Aptamers are single-stranded oligonucleotides that have a specific three-dimensional structure that allows them to bind to specific target molecules with high affinities. Aptamers have the potential to replace monoclonal antibodies because they present less immunogenicity and have an easier and a more cost-effective manufacturing process [16,17].…”
Section: Rna Therapeutics For Cancer Treatmentmentioning
confidence: 99%